The internet of things breakthroughs in research and practice - Information Resources Management Association (Hershey, Pennsylvania IGI Global, 2017)
"This book is an authoritative reference source for the latest academic material on the interconnectivity of networks and devices in the digital era and examines best practices for integrating this advanced connectivity across multiple fields. Featuring extensive coverage on innovative perspectives, such as secure computing, regulatory standards, and trust management"-- Provided by publisher.
Section 1. Community engagement and governance -- Section 2. Health and welfare -- Section 3. Security, privacy, and forensics -- Section 4. Strategic innovation and data management.
Includes bibliographical references.
Keywords: Internet of things; Internet of things -- Security measures; Electronic books